The knowledge of nurses about prevention of infections caused by the bacteria Clostridium difficile - Ivana Miljković; Amajla Topuz (Биомедицинска истраживања, 2021)
Introduction: Clostridium difficile is the leading cause of nosocomial diarrhea, associated with the use of antibiotics. The most common ways of transmitting the infection in hospitals are contaminated surfaces of the premises and the hands of medical staff. Methods: The study involved 68 nurses/technicians employed at the University Hospital Foca in the departments of surgery and internal medicine. As a research instrument, we used a specially designed questionnaire, created by the authors for the purpose of this research. Results: The research showed that 61.8% of respondents knew that hand washing with warm water and soap was considered the most effective prevention of the spread of infections, and 55.88% meant that they used chlorine-based preparations and hydrogen peroxide as the only effective disinfectant. Nurses with a work experience of less than 5 years showed better knowledge than other groups. Conclusion: The knowledge of nurses about the prevention of C. difficile infection is not at a satisfactory level, which indicates the growing need for education of nurses.
Keywords: Clostridium difficile; nurses’ knowledge; nosocomial infections